2009
DOI: 10.2353/ajpath.2009.080515
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Macrophages to Angiogenesis Induced by Vascular Endothelial Growth Factor Receptor-3-Specific Ligands

Abstract: Vascular endothelial growth factor receptor (VEGFR)-2 is a major stimulator of hemangiogenesis (HA), whereas VEGFR-3 stimulates lymphangiogenesis (LA). Contrary to this understanding, we demonstrate that implantation of pellets containing VEGFR-3-specific ligands (VEGF-C156S and recombinant murine VEGF-D) into the corneal stroma induce not only LA but also robust HA characterized by blood vessels that are positive for VEGFR-3 expression. The implantation of pellets containing VEGFR-3-specific ligands also lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 43 publications
4
63
0
1
Order By: Relevance
“…35,49,50 Previous reports have shown that systemic or local macrophage depletion inhibited pathological neovascularization in several ocular models. 33,34,[51][52][53] In our study, the majority of TLR4-and HMGB1-positive cells were F4/80 positive cells in the injured corneas. Moreover, in vitro, the main HMGB1-induced angiogenic factor from murine peritoneal macrophages of WT mice but not of TLR4 Ϫ/Ϫ mice was VEGF.…”
Section: Discussionsupporting
confidence: 54%
“…35,49,50 Previous reports have shown that systemic or local macrophage depletion inhibited pathological neovascularization in several ocular models. 33,34,[51][52][53] In our study, the majority of TLR4-and HMGB1-positive cells were F4/80 positive cells in the injured corneas. Moreover, in vitro, the main HMGB1-induced angiogenic factor from murine peritoneal macrophages of WT mice but not of TLR4 Ϫ/Ϫ mice was VEGF.…”
Section: Discussionsupporting
confidence: 54%
“…To approach this, we compared the number of macrophages in infant and adult corneas 1 week after suture placement using the standard protocol as described previously. 22,26,27 Our results from this assay revealed that the number of macrophages was significantly higher in infant than in adult corneas, as shown in Figure 5 (*P < 0.05).…”
Section: Infant Cornea Exhibits Enhanced Macrophage Infiltrationmentioning
confidence: 60%
“…Macrophage infiltration was also evaluated according to the standard protocol. 22,26,27 Briefly, total 10 areas (8 from the periphery and 2 from the center) of each sample were randomly picked and examined under the epifluorescence microscope. Total numbers of F4/80 positive cells were counted throughout the whole thickness of the picked area.…”
Section: Vascular and Macrophage Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…and upregulation or trends towards upregulation of Flt4, which participates in the recruitment of VEGF-A-secreting macrophages involved in angiogenesis [48], F3 and Mmp19 [49,50].…”
Section: Attempts To Compensate Perinatal Deleterious Effects In Islementioning
confidence: 99%